Factors Influencing Income Levels Of Fish Traders - Maksimiliana Ginting, Nina (Sean Institute, 2023)
This research is to look at the factors that influence the level of income of fish traders with the independent variable purchase price, selling price, labor and trading experience and the dependent variable income. The research was conducted at the Afternoon Market and Wamanggu Market. The population in the study were 15 tilapia fish traders. Sampling in this study used the Judgment sampling method. Simultaneously, all independent factors influence the dependent variable. Purchase prices, selling prices, labor and trading experience affect the income of fish traders at the Sore Market and Wamanggu Market. Partially, selling prices and labor have an effect on traders' income, while buying prices and trading experience have no effect on traders' income.